Sport Satellite Channels and their Effect in Provoking Football Prejudice of the Public: 衛星體育台對影響大眾足球的偏見 - Hassan, Amro; Badran , Ahmed (Asian Journal of Physical Education & Recreation, 2013)
The research aims to present a social reading to recognize the sports satellites’ effect in provoking sports spectators prejudice, the researcher used the descriptive method surveys, and the research community included analyzing two programs of two sports satellites channels, namely: Nile Sport and Modern Sport, both are transmitted on Nile sat and not encrypted. The sample was selected randomly of 1040 spectators: 760 males and 280 females of sports fans watching football on Nile Sport and Modern Sport. In achieving the aim of the research, a tool was prepared and used by the researcher, namely: a football prejudice and sport satellite channels scale, the present research adopted data analysis by SPSS statistical program using and built football prejudice and sport satellite channels scale, that consisted of 23 items divided into two factors: Group I(football prejudice - 13 items)-Group II (the content of satellite sports channels provoking football prejudice -10 items). The most important results came in as follows:(a) Percentage of football prejudice in Group I (sport prejudice) 74.9% among males, while it was 73.7% among females - 76.4% according to the residence of the countryside, while it was 72.3% according to the residence of the countries. And according to the educational level they were as follows: without 71.1%, average 72.8%- above the average 73.8% - university 72.4%. (b) Percentage of football prejudice in Group II(the content of Satellite Sports channels provoking football prejudice) 62.5% among males, while it was 78.1% among females -62.8% according to the residence of the countryside, while it was 76.8% according to the residence of the countries and according to the educational level they were as follows: 66.3% without - 68.5% average - 69.0% above the average - 72.5% university. The researcher recommended using a scale of football prejudice and sports satellite channels; as well as paying attention to the content of satellite sports programs; so as to contribute to reducing the provoking of football prejudice of football public spectators.